Preparation and Properties of Catalyst for Chlorine Dioxide Degrading Azo-Dye Simulated Wastewater Containing Reactive Brilliant Red KD-8B - Huang, Lijie; Nong, Guangzai; Wang, Shuangfei (Asian Journal of Chemistry, 2012)
The preparation and properties of a new ternary catalyst for chlorine dioxide catalytic oxidation were studied. The catalyst NiO-CuOx-La2O3/Al2O3 was prepared by the dipping-calcination method using activated alumina as a supporter. Optimum preparation conditions were as follows: the best volume ratio of Ni(NO3)2 and Cu(NO3)2 is 5:1; the optimal volume ratio of Ni(NO3)2 and La(NO3)3 is 40:9. The ternary catalyst had high catalytic activity and longer service life.